Canine sexual dimorphism in Egyptian Eocene anthropoid primates: Catopithecus and Proteopithecus - Simons, Elwyn L. (The National Academy of Sciences, 1999)
Two very small late Eocene anthropoid primates, Catopithecus browni and Proteopithecus sylviae, from Fayum, Egypt show evidence of substantial sexual dimorphism in canine teeth. The degree of dimorphism suggests that these early anthropoids lived in social groups with a polygynous mating system and intense male–male competition. Catopithecus and Proteopithecus are smaller in estimated body size than any living primates showing canine dimorphism. The origin of canine dimorphism and polygyny in anthropoids was not associated with the evolution of large body size.